TEACHERS’ READING HABITS AND THEIR EFFECT ON THE STUDENTS’ LITERACY - Hesni Neno; Ulu Emanuel; Delti Yulita (University of Kuningan, 2022)
This article is intended to show the importance of teachers’ reading habits to develop students’ literacy effectively. It is shown that the lack of teachers’ reading habits causing the deficiencies and lack of opportunity for students’ quality in EFL literacy. This study used mixed method approach and the data were collected through questionnaire, interview, reading test, and observation. The participants in this study were 6 teachers and 120 students from 6 schools. The result showed that teachers’ reading habits and affective states in EFL reading were in medium level and students’ literacy were in low level. It also exposed that teachers faced many reading problems and challenges throughout the years they studied English. There is a tendency that teachers’ deficiencies on their reading habits is from their perception about EFL reading that still focus on translating the words into their first language rather than critically involved with the main ideas in the text. The result concludes that teachers’ lack of reading habits had caused the lack opportunity of their students’ quality literacy instruction in the classroom. This lack of instruction caused the students are thriving and struggling as EFL readers who do not achieve proficiency, fluency, or comprehension. Moreover, there are also many factors that affect reading habits such as socio-economic background. Parents’ role and the development of technology that changes the medium of reading.